Space, time and political responsibility in the midst of global inequality - Massey, Doreen (ERDKUNDE, 2006)
This paper is the text of the First Annual Lecture in Development Geography, presented at the University of Bonn. It argues that the way in which space is conceptualised is of critical significance for the conduct of social sciences, here with particular reference to development geography. The paper begins with a proposal for the conceptualisation of space, and argues that if such a conceptualisation were taken seriously it would pose considerable challenges, both scientific and political. As a result of this, ‘weaker’ conceptualisations are frequently resorted to, in order to evade such challenges, and the second section of the paper explores two such ‘evasive imaginations’. The third section then takes up a particular case of identity and subjectivity and the different geographies potentially implied by different conceptualisations of them. This leads into the question of the geographies of responsibility, especially in a globalised era. The paper argues for a greater degree of ‘outward lookingness’ and puts the case that, again, the conceptualisation of space feeds into the idea of responsibility.